2015
DOI: 10.1097/shk.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Heparin Anticoagulation During Extracorporeal Life Support for Acute Respiratory Distress Syndrome in Conscious Sheep

Abstract: Background:Over 32% of burned battlefield causalities develop trauma-induced hypoxic respiratory failure, also known as acute respiratory distress syndrome (ARDS). Recently, 9 out of 10 US combat soldiers’ survived life-threatening trauma-induced ARDS supported with extracorporeal membrane oxygenation (ECMO), a portable form of cardiopulmonary bypass. Unfortunately, the size, incidence of coagulation complications, and the need for systematic anticoagulation for traditional ECMO devices have prevented widespre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In line with previous studies (23,24), ECMO was applied even in early post-traumatic or surgical patients and a relatively low aPTT of 35-40 was targeted. Lower and or delayed AC was safely used in experimental studies or in trauma patients (24,25). In one reported series of ECMO cases authors did not use any AC for a short time (26), although in one of these patients' multiple thrombus formations were detected in the inferior cava vein.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies (23,24), ECMO was applied even in early post-traumatic or surgical patients and a relatively low aPTT of 35-40 was targeted. Lower and or delayed AC was safely used in experimental studies or in trauma patients (24,25). In one reported series of ECMO cases authors did not use any AC for a short time (26), although in one of these patients' multiple thrombus formations were detected in the inferior cava vein.…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently published that ECMO without continuous heparinization could sustain a circuit up to 10 hours. 6 Moreover, several case reports have concluded that is safe to discontinue systemic heparinization in traumatic bleeding patients requiring ECMO. 18 We documented the first SEM analysis of MOs using a trauma-related ARDS ECMO model.…”
Section: Discussionmentioning
confidence: 99%
“…Based on other studies the change in shear stress applied to blood as it enters the MO activates the clotting cascade facilitating the greatest potential for clots. 6 Both methods achieved the goal of SEM analysis of the PMP fibers, allowing for a more conclusive post-ECMO assessment of the MOs. Although both methods differ in basic approach, we are confident that they are both useful in providing insight into the dynamics of clot formation on MOs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations